The effects of task load, social support, and academic self-efficacy on students’ academic stress: Testing the moderating role of study program - Inayah Ridhayanti Qarimah; A. Muhajir Nasir; Syamsuriah Syamsuriah (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2026)
Academic stress remains a major concern in higher education because it can undermine students’ well-being, learning engagement, and academic performance. This study examined the effects of task load, social support, and academic self-efficacy on students’ academic stress, and tested whether study program moderated these relationships. Using a quantitative cross-sectional survey design, data were collected from 368 students in three teacher education programs at Universitas Negeri Makassar: Elementary School Teacher Education, Guidance and Counseling, and Family Welfare Education. Participants were selected through proportionate stratified random sampling. Likert-scale questionnaires were used to measure task load, social support, academic self-efficacy, and academic stress, with all instruments showing strong internal consistency. Data were analyzed using multiple linear regression and Moderated Regression Analysis. The results showed that task load was the strongest positive predictor of academic stress, while academic self-efficacy had a significant negative effect. Social support did not significantly predict academic stress, and study program did not moderate the tested relationships. The model explained 42.8% of the variance in academic stress. These findings indicate that academic stress is shaped more by perceived workload and internal psychological resources than by study program differences, highlighting the importance of proportional workload management and self-efficacy development.